3D-printed rolling circle amplification chip for on-site colorimetric detection of inorganic mercury in drinking water. (1st December 2019) - Lim, Ji Won; Kim, Tai-Yong; Choi, Sung-Wook; Woo, Min-Ah
Highlights: A platform for colorimetric Hg 2+ detection with a 3D-printed chip was developed. Hg 2+ detection by a "turn-off"-type reaction was based on T-Hg 2+ -T interaction. The lowest Hg 2+ level in tap water was experimentally quantified as 3.6 μg/L. RCA efficiency on the chip was improved by using a double-repeat DNAzyme. Our low-cost on-site testing system can prevent accidental Hg 2+ poisoning. Abstract: A point-of-care testing chip was developed for the colorimetric detection of inorganic mercury ion (Hg 2+ ). The disposable chip fabricated by three-dimensional printing technology contains DNAzymes produced by rolling circle amplification (RCA); a color change caused by the enzymatic reaction between DNAzymes and the peroxidase substrate 2, 2′-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) is measured using a portable spectrophotometer. In the "turn-off"-type RCA reaction, the annealing of the T(12) primer that initiates the RCA reaction is blocked by the interaction of thymine with Hg 2+ ; thus, the amount of amplified DNAzymes causing a color change is decreased depending on Hg 2+ concentration. The colorimetric signal is enhanced by amplifying double-repeat DNAzymes from a circular DNA template. The chip detected Hg 2+ in tap drinking water samples with high sensitivity (lowest validated value: 3.6 μg/L) and showed better selectivity, precision, and reproducibility than conventional analysis instruments. This low-cost easy-to-use platform can reduce the risk of accidental Hg 2+ poisoning.